Sodium battery cell preparation process capable of reducing flatulence, sodium battery cell and sodium battery
By using double-sided glue-coated single-sided ceramic diaphragm combined with hot pressing process in the sodium battery cell, and performing high-temperature, extrusion, and vacuum negative pressure synthesis processes, the problem of sodium battery cell inflation at high temperatures is solved, significantly improving the safety and service life of the battery cell.
Patent Information
- Application Number
- CN202411982303.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
The sodium battery cell has a gas bloating after high temperature storage and long-term circulation, resulting in an increase in internal pressure, deformation of the battery cell, and even possible leakage and burst, seriously affecting the safety and service life of the sodium battery.
The battery cell is prepared by double-sided glue-coated single-sided ceramic diaphragm combined with hot pressing process, and the released gas is further discharged under high-charge state, high temperature and extrusion through high-temperature, extrusion, vacuum negative pressure, high charging limit voltage, and cyclic charge and discharge.
It effectively reduces the diffusion distance of sodium ions and gas residue during charging and discharging, reduces the gas bloating phenomenon of sodium battery cells in high temperature environments, and improves the safety and service life of the battery cells.
Smart Images

Figure BDA0005221812790000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field, and in particular to a sodium battery cell preparation process for reducing flatulence, a sodium battery cell and a sodium battery. Background Art
[0002] With the continuous development of new energy vehicles and energy storage markets, the requirements for battery energy density, safety, and cost are also increasing. Among many batteries, sodium-ion batteries (hereinafter referred to as sodium batteries) have attracted widespread attention due to their abundant raw material resources, energy density much higher than lead-acid batteries, and performance close to that of lithium batteries. However, after high-temperature storage and long-term circulation, the battery cells will experience bloating, which is mainly manifested in increased internal pressure, deformation of the battery cells, and even possible leakage and explosion, which seriously affects the high safety and long-term use of sodium batteries. Therefore, it is urgent to solve the bloating problem of sodium batteries. Summary of the invention
[0003] In order to solve at least one of the above technical problems, a sodium battery cell is developed to reduce the flatulence phenomenon in a high temperature environment. The present application provides a sodium battery cell preparation process for reducing flatulence, a sodium battery cell and a sodium battery.
[0004] On the one hand, the present application provides a process for preparing a sodium battery cell with reduced flatulence, comprising the following steps:
[0005] S1. Core making
[0006] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side; the glue layer has a thickness of 1 to 5 μm, and the ceramic layer has a thickness of 1 to 5 μm;
[0007] S2, flat pressure
[0008] The prepared battery cell is preheated at high temperature and then flat-pressed at high temperature; the preheating process parameters are set as follows: temperature of 80-100°C, heating time of 30-60min; the flat-pressing process parameters are set as follows: temperature of 80-100°C, pressure of 4-10T, flat-pressing time of 60-120s;
[0009] S3. Assembly
[0010] The flat-pressed battery cells are assembled, baked, and injected with liquid in sequence; and then the injection holes are sealed and the volume is divided after the formation process and activation process to obtain aluminum shell sodium ion battery cells;
[0011] The chemical formation process is:
[0012] After the injection, the battery cell is charged and discharged for 1 to 5 times at a temperature of 40 to 70°C, a squeeze pressure of 100 to 500 kgf, a vacuum degree of -40 to -90 KPa, and a formation voltage 0.05 to 0.25 V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage;
[0013] The activation process is:
[0014] After the formation, the battery cell is left to stand for 24 to 72 hours at a temperature of 40 to 60°C, an extrusion pressure of 200 to 600 kgf, and a vacuum degree of -30 to -60 KPa.
[0015] Optionally, in the core making step S1, the thickness of the glue layer is 2 to 4 μm;
[0016] And / or, the thickness of the ceramic layer is 2 to 4 μm.
[0017] Optionally, in the core making step S1, the material of the adhesive layer is PVDF or PMMA;
[0018] And / or, the material of the ceramic layer is Al 2 O 3 Or a type of boehmite.
[0019] Optionally, in the S2 flat pressing, the preheating process parameters are set as: temperature 85-95° C.; heating time 40-50 min.
[0020] Optionally, in the S2 flat pressing, the flat pressing process parameters are set as: temperature 85-95° C., pressure 5-8T, and flat pressing time 80-100s.
[0021] Optionally, in the S3 assembly, the formation process is as follows: the battery cell after liquid injection is charged and discharged 2 to 4 times at a temperature of 45 to 60°C, an extrusion pressure of 200 to 400 kgf, a vacuum degree of -60 to -80 Kpa, a formation voltage 0.10 to 0.20 V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage.
[0022] Optionally, in the S3 assembly, the activation process is: the battery cell after formation is allowed to stand for 36 to 60 hours at a temperature of 45 to 55° C., an extrusion pressure of 300 to 500 kgf, and a vacuum degree of -40 to -50 KPa.
[0023] In a second aspect, the present application provides a sodium battery cell prepared using the above-mentioned preparation process.
[0024] In a third aspect, the present application provides a sodium battery comprising the above-mentioned sodium battery cell.
[0025] In summary, the present invention includes at least one of the following beneficial technical effects:
[0026] 1. The stacked core / wound core adopts double-sided glue coating and single-sided ceramic diaphragm with hot pressing process to achieve close fit between the positive and negative pole pieces of the stacked core / wound core and the diaphragm, reduce the diffusion distance of sodium ions and gas residue during charging and discharging;
[0027] 2. The high temperature, extrusion, vacuum negative pressure, high charging limit voltage, and cyclic charge and discharge formation processes have the functions of accelerating the electrode electrolyte interface reaction, achieving close fitting between the stacked / wound core electrode and the diaphragm, facilitating the discharge of gas production, and fully releasing the gas produced by the interface reaction;
[0028] 3. After formation, the released gas is further discharged under high charge state, high temperature and extrusion;
[0029] 4. Through the improvement of the process of this application, the gas production of sodium ion batteries during charging and discharging can be reduced, especially the gas production in high temperature environments, so that they can be used safely for a long time in high temperature environments. DETAILED DESCRIPTION
[0030] The present application is further described in detail below with reference to the embodiments.
[0031] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments
[0033] Example 1
[0034] This embodiment is used to prepare a sodium battery cell preparation process for reducing flatulence, comprising the following steps:
[0035] S1. Core making
[0036] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0037] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0038] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0039] S2, flat pressure
[0040] The prepared battery cell is preheated at high temperature, and the preheating process parameters are set as follows: temperature is 90°C, and heating time is 40 minutes.
[0041] After preheating, high-temperature flat pressing is performed; the flat pressing process parameters are set as: temperature 90°C, pressure 5T, and flat pressing time 90s.
[0042] S3. Assembly
[0043] The flat pressed cells are assembled, baked and injected with liquid in sequence; the cells after injection are charged and discharged three times at a temperature of 45°C, an extrusion pressure of 300kgf, a vacuum degree of -70KPa, and a formation voltage 0.1V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; the highly charged cells after formation are left to stand for 48 hours at a temperature of 45°C, an extrusion pressure of 300kgf, and a vacuum degree of -40KPa. The injection hole is then sealed and the volume is divided to obtain an aluminum shell sodium ion cell.
[0044] Example 2
[0045] This embodiment is used to prepare a sodium battery cell preparation process for reducing flatulence, comprising the following steps:
[0046] S1. Core making
[0047] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0048] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0049] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0050] S2, flat pressure
[0051] The prepared battery cell is preheated at high temperature, and the preheating process parameters are set as follows: temperature is 90°C, and heating time is 30 minutes.
[0052] After preheating, high-temperature flat pressing is performed; the flat pressing process parameters are set as: temperature 90°C, pressure 5T, and flat pressing time 60s.
[0053] S3. Assembly
[0054] The flat-pressed cells are assembled, baked, and injected with liquid in sequence; the cells after injection are charged and discharged once at a temperature of 45°C, an extrusion pressure of 200kgf, a vacuum degree of -60KPa, and a formation voltage 0.05V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; the highly charged cells after formation are left to stand for 24 hours at a temperature of 45°C, an extrusion pressure of 200kgf, and a vacuum degree of -30KPa. The injection hole is then sealed and the volume is divided to obtain an aluminum shell sodium ion cell.
[0055] Example 3
[0056] This embodiment is used to prepare a sodium battery cell preparation process for reducing flatulence, comprising the following steps:
[0057] S1. Core making
[0058] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0059] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0060] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0061] S2, flat pressure
[0062] The prepared battery cell is preheated at high temperature, and the preheating process parameters are set as follows: temperature is 80°C, and heating time is 30 minutes.
[0063] After preheating, high-temperature flat pressing is performed; the flat pressing process parameters are set as: temperature 80°C, pressure 5T, and flat pressing time 60s.
[0064] S3. Assembly
[0065] The flat pressed cells are assembled, baked and injected with liquid in sequence; the cells after injection are charged and discharged 4 times at a temperature of 50°C, an extrusion pressure of 300kgf, a vacuum degree of -80KPa, and a formation voltage 0.1V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; the highly charged cells after formation are left to stand for 60 hours at a temperature of 50°C, an extrusion pressure of 300kgf, and a vacuum degree of -40KPa. The injection hole is then sealed and the volume is divided to obtain an aluminum shell sodium ion cell.
[0066] Comparative Example 1
[0067] This comparative example provides a sodium battery cell preparation process for reducing flatulence, which is different from Example 1 in that the preparation process of this comparative example does not perform a flattening process, and specifically includes the following steps:
[0068] S1. Core making
[0069] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0070] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0071] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0072] S2. Assembly
[0073] The flat pressed cells are assembled, baked and injected with liquid in sequence; the cells after injection are charged and discharged three times at a temperature of 45°C, an extrusion pressure of 300kgf, a vacuum degree of -70KPa, and a formation voltage 0.1V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; the highly charged cells after formation are left to stand for 48 hours at a temperature of 45°C, an extrusion pressure of 300kgf, and a vacuum degree of -40KPa. The injection hole is then sealed and the volume is divided to obtain an aluminum shell sodium ion cell.
[0074] Comparative Example 2
[0075] This comparative example provides a sodium battery cell preparation process for reducing flatulence, which is different from Example 2 in that the preparation process of this comparative example does not perform the formation process in the assembly step, and specifically includes the following steps:
[0076] S1. Core making
[0077] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0078] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0079] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0080] S2, flat pressure
[0081] The prepared battery cell is preheated at high temperature, and the preheating process parameters are set as follows: temperature is 90°C, and heating time is 30 minutes.
[0082] After preheating, high-temperature flat pressing is performed; the flat pressing process parameters are set as: temperature 90°C, pressure 5T, and flat pressing time 60s.
[0083] S3. Assembly
[0084] The flat pressed battery cells are assembled, baked and injected with liquid in sequence; the injected battery cells are charged to the charging cut-off voltage, and then left to stand for 24 hours at a temperature of 45°C, a pressing force of 200kgf and a vacuum degree of -30KPa. The injection holes are then sealed and the volume is divided to obtain aluminum shell sodium ion battery cells.
[0085] Comparative Example 3
[0086] This comparative example provides a process for preparing a sodium battery cell with reduced flatulence, which is different from Example 3 in that the preparation process of this comparative example does not perform the activation process in the assembly step, and specifically includes the following steps:
[0087] S1. Core making
[0088] The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side.
[0089] The adhesive layer is exemplarily made of PVDF material, and has an exemplary thickness of 2 μm.
[0090] The ceramic layer is exemplarily made of boehmite and has a thickness of 2 μm.
[0091] S2, flat pressure
[0092] The prepared battery cell is preheated at high temperature, and the preheating process parameters are set as follows: temperature is 80°C, and heating time is 30 minutes.
[0093] After preheating, high-temperature flat pressing is performed; the flat pressing process parameters are set as: temperature 80°C, pressure 5T, and flat pressing time 60s.
[0094] S3. Assembly
[0095] The flat-pressed battery cells are assembled, baked and injected with liquid in sequence; the battery cells after injection are charged and discharged 4 times in a cycle at a temperature of 50°C, an extrusion pressure of 300kgf, a vacuum degree of -80KPa, and a formation voltage 0.1V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; the injection hole is sealed and the capacity is divided to obtain an aluminum shell sodium ion battery cell.
[0096] The thickness and thickness expansion rate of the battery cells of Examples 1 to 3 and Comparative Examples 1 to 3 before and after storage at 55° C. for 7 days are shown in Table 1.
[0097] Table 1
[0098]
[0099]
[0100] It can be seen from Examples 1 to 3, Comparative Examples 1 to 3 and Table 1 that the battery cells prepared in the present application have a thickness expansion rate lower than 1.8% after being stored at 55°C for 7 days, which is much lower than the expansion rate of about 7% in Comparative Examples 1 to 3. This indicates that the battery cells prepared by the technical solution of the present application are stored at a high temperature of 55°C, and the flatulence phenomenon is significantly reduced compared with Comparative Examples 1 to 3, and the battery cells of the present application can be better used for a long time in a high temperature environment.
[0101] The charge retention rate and capacity recovery rate of the cells of Examples 1 to 3 and Comparative Examples 1 to 3 before and after storage at 55° C. for 7 days are shown in Table 2.
[0102] Table 2
[0103] experiment Charge retention rate Capacity recovery rate Example 1 95.5% 96.3% Example 2 96.2% 97.5% Example 3 95.3% 96.7% Comparative Example 1 92.6% 94.2% Comparative Example 2 91.8% 93.5% Comparative Example 3 92.3% 93.8%
[0104] It can be seen from Examples 1 to 3, Comparative Examples 1 to 3 and Table 2 that the battery cell prepared in the present application can achieve a charge retention rate of more than 95% after being stored at 55°C for 7 days, which is much higher than the charge retention rate of about 92% in Comparative Examples 1 to 3; the capacity recovery rate can reach more than 96%, which is much higher than the capacity recovery rate of about 94% in Comparative Examples 1 to 3. The battery cell of the present application is used for a long time in a high temperature environment, and its energy storage performance decreases more slowly than that of the comparative example, and is more suitable for use in a high temperature environment.
[0105] The capacities and capacity retention rates of Examples 1 to 3 and Comparative Examples 1 to 3 before and after 500 cycles at 25° C. are shown in Table 3.
[0106] Table 3
[0107] experiment Initial capacity (Ah) Capacity after 500 cycles (Ah) Capacity retention rate Example 1 32.13 30.15 93.8% Example 2 32.06 29.83 93.0% Example 3 32.42 29.74 91.7% Comparative Example 1 31.79 26.78 84.2% Comparative Example 2 31.68 26.31 83.0% Comparative Example 3 32.17 28.25 87.8%
[0108] It can be seen from Examples 1 to 3, Comparative Examples 1 to 3 and Table 3 that the capacity retention rate of the battery cell prepared in the present application can reach 91.7% or more after 500 cycles at 25°C, which is significantly higher than the capacity retention rate of less than 88% in Comparative Examples 1 to 3. This indicates that the cycle life of the battery cell prepared in the present application at room temperature is also higher than that of Comparative Examples 1 to 3.
[0109] The thickness and thickness expansion rate of the battery cells of Examples 1 to 3 and Comparative Examples 1 to 3 before and after 500 cycles at 25° C. are shown in Table 4.
[0110] Table 4
[0111] experiment Thickness before cycle (mm) Thickness before cycle (mm) Thickness growth rate Example 1 27.62 28.24 2.2% Example 2 27.75 28.47 2.6% Example 3 27.82 28.58 2.7% Comparative Example 1 27.93 29.96 7.3% Comparative Example 2 27.72 30.15 8.8% Comparative Example 3 27.84 29.92 7.5%
[0112] It can be seen from Examples 1 to 3, Comparative Examples 1 to 3 and Table 3 that the battery cells prepared in the present application have a thickness growth rate of less than 2.7% after 500 cycles at room temperature compared with the comparative examples, which is much lower than the thickness growth rate of more than 7.3% in comparative examples 1 to 3. This indicates that the battery cells prepared by the technical solution of the present application are stored at room temperature, and the bloating phenomenon is also significantly reduced compared with comparative examples 1 to 3, and the battery cells of the present application can be better used for a long time under room temperature conditions.
[0113] It can be seen from Examples 1 to 3, Comparative Examples 1 to 3 and Tables 1 to 4 that the electrochemical performance of the battery cell prepared in the present application is significantly higher than that of Comparative Examples 1 to 3 at room temperature and high temperature, and the flatulence phenomenon is much lower than that of Comparative Examples 1 to 3. The service life of the battery cell prepared in the present application is significantly higher than that of Comparative Examples 1 to 3.
[0114] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A process for preparing a sodium battery cell with reduced flatulence, characterized in that: The following steps are involved: S1. Core making The separator is stacked / wound to obtain a battery core; the separator is coated with a glue layer on both sides and a ceramic layer on one side; the glue layer has a thickness of 1 to 5 μm, and the ceramic layer has a thickness of 1 to 5 μm; S2, flat pressure The prepared battery cell is preheated at high temperature and then flat-pressed at high temperature; the preheating process parameters are set as follows: temperature of 80-100°C, heating time of 30-60min; the flat-pressing process parameters are set as follows: temperature of 80-100°C, pressure of 4-10T, flat-pressing time of 60-120s; S3. Assembly The flat-pressed battery cells are assembled, baked, and injected with liquid in sequence; and then the injection holes are sealed and the volume is divided after the formation process and activation process to obtain aluminum shell sodium ion battery cells; The chemical formation process is: After the injection, the battery cell is charged and discharged for 1 to 5 times at a temperature of 40 to 70°C, a squeeze pressure of 100 to 500 kgf, a vacuum degree of -40 to -90 KPa, and a formation voltage 0.05 to 0.25 V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage; The activation process is: After the formation, the battery cell is left to stand for 24 to 72 hours at a temperature of 40 to 60°C, an extrusion pressure of 200 to 600 kgf, and a vacuum degree of -30 to -60 KPa.
2. The preparation process according to claim 1, characterized in that: In the S1 core making, the thickness of the glue layer is 2 to 4 μm; And / or, the thickness of the ceramic layer is 2 to 4 μm.
3. The preparation process according to claim 1, characterized in that: In the core making of S1, the material of the adhesive layer is one of PVDF and PMMA; And / or, the material of the ceramic layer is Al2O3 or boehmite.
4. The preparation process according to claim 1, characterized in that: In the S2 flat pressing, the preheating process parameters are set as: temperature 85-95° C.; heating time 40-50 min.
5. The preparation process according to claim 1, characterized in that: In the S2 flat pressing, the flat pressing process parameters are set as: temperature 85-95° C., pressure 5-8T, and flat pressing time 80-100s.
6. The preparation process according to claim 1, characterized in that: In the S3 assembly, the formation process is as follows: the battery cell after injection is charged and discharged 2 to 4 times at a temperature of 45 to 60°C, an extrusion pressure of 200 to 400 kgf, a vacuum degree of -60 to -80 Kpa, a formation voltage 0.10 to 0.20 V higher than the charge cut-off voltage, and then charged to the charge cut-off voltage.
7. The preparation process according to claim 1, characterized in that: In the S3 assembly, the activation process is as follows: the battery cell after formation is left to stand for 36 to 60 hours at a temperature of 45 to 55° C., an extrusion pressure of 300 to 500 kgf, and a vacuum degree of -40 to -50 KPa.
8. A sodium battery cell, characterized in that: The preparation is obtained by the preparation process described in claim 1.
9. A sodium battery, characterized in that: The invention comprises the sodium battery cell as claimed in claim 8.